Implementasi Standar Pelayanan Minimal Di IGD RSUD I Lagaligo Wotu - Anas Budi; Desak Nyoman Suartini; Andi Syamsul Bachru Jamal (HEALTH CARE : JURNAL KESEHATAN, 2020)
Hospital Minimum Service Standards (SPM) are provisions for hospitals issued by the Minister of Health of the Republic of Indonesia in the context of government efforts to ensure the quality of hospital services. This Minimum Service Standard can be used as a guideline for the quality of service for every hospital in Indonesia. This research aimed to study the infrastructure and human resources with implementation of minimum service standards in the Emergency Department (IGD) Regional General Hospital (RSUD) I Lagaligo, East Luwu. The research used in this research is quantitative with a cross-sectional approach, in which all observed variables are measured simultaneously when the research is taking place. This research was conducted in the Emergency Room Installation Room (IGD) Regional General Hospital (RSUD) I Lagaligo East Luwu. Sample selection with total sampling technique. The research subjects were 33 nurses in the IGD Lagaligo Wotu East Luwu Regional Hospital. The results showed that the results of the bivariate analysis used the Chi-Square Test. It shows that there is a relationship between infrastructure with implementation of minimum service standards with a value of p = 0.008, and there is a relationship between human resources with implementation of minimum service standards with a value of p = 0.000.